2003
DOI: 10.1177/000348940311201110
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Severe Taste Loss in a Chemosensory Clinic Population

Abstract: Although complete or near-complete olfactory loss has been extensively documented and described, few published reports have documented severe generalized gustatory loss (across qualities and neural fields) with rigorous psychophysical testing, and none have explored the prevalence or causes of such losses in a large clinical population. This study retrospectively reviews our chemosensory clinic's experience of 1,176 patients evaluated for complaints of chemosensory dysfunction in order to address these issues.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 31 publications
4
82
1
2
Order By: Relevance
“…However, women who currently smoked had higher sucrose detection thresholds, albeit within normal clinical range (Pribitkin et al, 2003), when compared to never smokers who were matched for age, race, body mass index, income, and phase of the menstrual cycle. The greater the cumulative smoking dose pack-years, the greater the decline in sucrose taste sensitivity.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…However, women who currently smoked had higher sucrose detection thresholds, albeit within normal clinical range (Pribitkin et al, 2003), when compared to never smokers who were matched for age, race, body mass index, income, and phase of the menstrual cycle. The greater the cumulative smoking dose pack-years, the greater the decline in sucrose taste sensitivity.…”
Section: Discussionmentioning
confidence: 85%
“…one in which positive and negative reversals are achieved at successively higher concentrations). These additional criteria ensure a more stable measure of the threshold attained (see Pribitkin et al, 2003). The threshold concentration was then calculated as the mean of the log values of the last 4 reversals.…”
Section: Sucrose Detection Thresholdsmentioning
confidence: 99%
“…The latter is an especially important finding because individuals with taste impairment are rarely seen in specialized centers [4,33]. The observed lack of distinct age-dependent changes in taste function may be the result of the relative insensitivity of the applied gustatory test.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study examining 1,176 patients with chemosensory complaints found generalised taste disorders for all four taste qualities in only 10 (0.85%) patients. Half of these patients were classified as severe hypogeusic and half as ageusic [22], even though 8.1% were found to exhibit quality specific elevations in taste thresholds [22]. In the ''Beaver Dam Offspring Study'' taste discs of the qualities salty, sweet, sour, bitter and PROP were used to test taste function in 2,733 healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The reported data exhibit great variation. Rates for generalised ageusia range from 0.84 [22] to ''below 4%'' [5] in patients complaining about gustatory disorders and up to almost 20% [27] in ''healthy subjects''. However, direct comparison of the different studies is difficult, especially since different tests are applied and test results were interpreted differently.…”
Section: Introductionmentioning
confidence: 99%